Perencanaan Strategis Kelurahan Kenep dalam Meningkatkan Perekonomian Masyarakat melalui Desa Wisata Kreatif - Hosana Opalia Waluyati; Kristina Setyowati (Jurnal Mahasiswa Wacana Publik, 2022)
Tourism is the largest and strongest sector that contributes to the global economy today. Efforts that can be applied to develop tourism in Indonesia are by developing alternative tourism by establishing tourist villages. Kenep Village is one of the areas that has developed itself into a Creative Tourism Village in Sukoharjo Regency. However, there are still obstacles in its development. The purpose of the study was to determine the strategic planning carried out by the Kenep Village Government based on the Tourism Awareness Group (Pokdarwis) of Kenep Creative Tourism Village in developing and maximizing their potential to improve the community's economy. The strategic planning proposed by John Bryson became a literature review in this study. To determine strategic issues, the litmus test is used. This type of research is descriptive qualitative and the data collection techniques used are interviews, observation, and documentation studies. The collected data was then analyzed using the SWOT analysis technique. The results of the study obtained three strategic issues in Kenep Creative Tourism Village, namely: (1) Developing facilities and infrastructure to support tourism as well as efforts for growth and equitable development, (2) Optimizing marketing and promotion through social media or digital-based online platforms to support progress of science and technology in the Kenep Creative Tourism Village, (3) Improving the ability and competence of the community to become a reliable and qualified workforce.